2012
DOI: 10.11159/ijecs.2012.001
|View full text |Cite
|
Sign up to set email alerts
|

Constrained Nonlinear Least Squares: A Superlinearly Convergent Projected Structured Secant Method

Abstract: Numerical solution of nonlinear least-squares problems is an important computational task in science and engineering. Effective algorithms have been developed for solving nonlinear least squares problems. The structured secant method is a class of efficient methods developed in recent years for optimization problems in which the Hessian of the objective function has some special structure. A primary and typical application of the structured secant method is to solve the nonlinear least squares problems. We pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…As such, there are numerous COP measures such as average velocity of COP, COP excursion, average radial displacement of the COP, to name a few; however until recently it was not evident which measure is optimal [ 8 ]. Mahdavi-Amiri et al have shown that during static posturography the average velocity for a given stability condition, is more repeatable (less variable) between trials from a data collection session, and more discernible between the different stability conditions [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…As such, there are numerous COP measures such as average velocity of COP, COP excursion, average radial displacement of the COP, to name a few; however until recently it was not evident which measure is optimal [ 8 ]. Mahdavi-Amiri et al have shown that during static posturography the average velocity for a given stability condition, is more repeatable (less variable) between trials from a data collection session, and more discernible between the different stability conditions [ 9 ].…”
Section: Introductionmentioning
confidence: 99%